High-pressure-sprayed double stranded RNA does not induce RNA interference of a reporter gene - Uslu, Veli Vural; Bassler, Alexandra; Krczal, Gabi; Wassenegger, Michael (Frontiers in plant science, 2020)
In plants, RNA interference (RNAi) is an effective defense mechanism against pathogens and pests. RNAi mainly involves the micro RNA and the small interfering RNA (siRNA) pathways. The latter pathway is generally based on the processing of long double stranded RNAs (dsRNA) into siRNAs by DICER-LIKE endonucleases (DCLs). SiRNAs are loaded onto ARGONAUTE proteins to constitute the RNA-induced silencing complex. Natural dsRNAs derive from transcription of inverted repeats or of specific RNA molecules that are transcribed by RNA-DIRECTED RNA POLYMERASE 6. Moreover, replication of infecting viruses/viroids results in the production of dsRNA intermediates that can serve as substrates for DCLs. The high effectiveness of RNAi both locally and systemically implicated that plants could become resistant to pathogens, including viruses, through artificial activation of RNAi by topical exogenous application of dsRNA. The most preferable procedure to exploit RNAi would be to simply spray onto mature plants naked dsRNAs that are specific for the attacking pathogens serving as a substitute for pesticides applications. However, the plant cell wall is a difficult barrier to overcome and only few reports claim that topical application of naked dsRNA triggers RNAi in plants. Using a transgenic Nicotiana benthamiana line, we found that high-pressure-sprayed naked dsRNA did not induce silencing of a GREEN FLUORESCENCE PROTEIN (GFP) reporter gene. Small RNA sequencing (sRNA-seq) of samples from sprayed leaves revealed that the dsRNA was, if at all, not efficiently processed into siRNAs indicating that the dsRNA was insufficiently taken up by plant cells.
Gesehen am 28.01.2020